2011
DOI: 10.2135/cropsci2010.05.0248
|View full text |Cite
|
Sign up to set email alerts
|

Shade and Traffic Tolerance Varies for Bermudagrass and Zoysiagrass Cultivars

Abstract: Bermudagrass (Cynodon spp.) and zoysiagrass [Zoysia spp. (Willd.)] are two of the most commonly used turfgrass species in the southern United States. Shade from trees is common on golf courses and limits turfgrass growth. Additionally, turfgrasses used on golf courses and sports fields are often subjected to traffic. The objective of this study was to evaluate shade and traffic effects on bermudagrass and zoysiagrass. Two shade treatments were imposed, full sun or 49% shade, using a light reducing fabric. A Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 11 publications
8
51
1
Order By: Relevance
“…Similar to previous studies (Busey and Davis, 1991;Jiang et al, 2004;Bunnell et al, 2005a;Trappe et al, 2011), our study found that three bermudagrass cultivars had a higher DLI requirement to maintain acceptable TQ than cultivars in other species. Different shade levels can vary in studies conducted in different locations; therefore, quantification of a DLI requirement is more comparable across studies and offers a more practical method for cultivar evaluation and selection.…”
Section: Comparative DLI Requirementsupporting
confidence: 91%
“…Similar to previous studies (Busey and Davis, 1991;Jiang et al, 2004;Bunnell et al, 2005a;Trappe et al, 2011), our study found that three bermudagrass cultivars had a higher DLI requirement to maintain acceptable TQ than cultivars in other species. Different shade levels can vary in studies conducted in different locations; therefore, quantification of a DLI requirement is more comparable across studies and offers a more practical method for cultivar evaluation and selection.…”
Section: Comparative DLI Requirementsupporting
confidence: 91%
“…The cultivars Patriot, Riviera, Tifsport, and Tifway bermudagrass, and Meyer and Diamond zoysiagrass had the best ball lie in unmown conditions, while Palisades had the poorest ball lie in unmown conditions. These results along with data on traffic tolerance (40) and divot resistance (38) and recovery (39) will assist golf course superintendents in selecting cultivars of bermudagrass and zoysiagrass well‐adapted for golf course fairways or tees that contain low clipping yields and scalping tendencies as well as a good golf ball lie in order to help to reduce plant growth regulator use, equipment wear, and labor and fuel costs associated with maintaining a golf course turf.…”
Section: Discussionmentioning
confidence: 99%
“…It was unclear why Patriot bermudagrass scalped more than other cultivars, but it may be because of Patriot's aggressive growth rate and high shoot density (19,28,37). Another possible explanation may be due to shortening of daylength and Patriot's susceptibility to decreased light intensity (2,40).…”
Section: Differences In Scalping Tendencymentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a great deal of research on zoysiagrass since 1990. Various environmental stresses including cold temperature (18,32,38) and drought tolerance (4,9,27,60), divot recovery (26,55), salinity tolerance (30,41), shade tolerance (49,53,56), and various biotic stresses including insect resistance (5,6,11,12,25,42,43,44,45,46,48,52), mite resistance (47), disease resistance (31), and nematode resistance (35,51) has been studied for many commonly used zoysiagrass cultivars. Zoysiagrass growth characteristics have also been studied including rooting (29), stolon growth (40), establishment (10,21,40), and clipping yield (57).…”
Section: Introductionmentioning
confidence: 99%